2018
DOI: 10.1016/j.marpolbul.2018.01.059
|View full text |Cite
|
Sign up to set email alerts
|

Habitat characteristics provide insights of carbon storage in seagrass meadows

Abstract: Seagrass meadows provide multiple ecosystem services, yet they are among the most threatened ecosystems on earth. Because of their role as carbon sinks, protection and restoration of seagrass meadows contribute to climate change mitigation. Blue Carbon strategies aim to enhance CO sequestration and avoid greenhouse gasses emissions through the management of coastal vegetated ecosystems, including seagrass meadows. The implementation of Blue Carbon strategies requires a good understanding of the habitat charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
115
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(140 citation statements)
references
References 146 publications
5
115
1
3
Order By: Relevance
“…Many habitat characteristics have been shown to influence the carbon content of seagrass meadow sediments, including seagrass species composition, canopy complexity, hydrodynamic regime, water depth, nutrient availability, and biotic interactions (Mazarrasa et al, ). Here we observed notable variability in sediment carbon content (percentage and stocks) as well as carbon sequestration rates both among and within regions.…”
Section: Discussionmentioning
confidence: 99%
“…Many habitat characteristics have been shown to influence the carbon content of seagrass meadow sediments, including seagrass species composition, canopy complexity, hydrodynamic regime, water depth, nutrient availability, and biotic interactions (Mazarrasa et al, ). Here we observed notable variability in sediment carbon content (percentage and stocks) as well as carbon sequestration rates both among and within regions.…”
Section: Discussionmentioning
confidence: 99%
“…The climate and geomorphology of water bodies along the coasts of each country region have resulted in hydrological differences related to fresh water inputs, hydroperiods, tidal ranges, hydrodynamics, and nutrient supplies and the presence of stressors that could influence the stocks and flux (import/export rates) of C org in mangroves and seagrasses (Woodroffe, 1992;Twilley & Rivera-Monroy, 2005;Fourqurean et al, 2012a;Mazarrasa et al, 2018). Figure 6 Seagrasses's C org stocks by geographic regions of Mexico.…”
Section: Mexico's Blue Carbon In Contextmentioning
confidence: 99%
“…Several studies have investigated the drivers behind Blue Carbon storage, and it has been shown that they consist of a complex set of physical, chemical, and biological factors that vary considerably between and within systems and are highly dependent on which functional scale is assessed (e.g., spatial, temporal, species, community, ecosystem) (see e.g., Ricart et al, 2015;Röhr et al, 2016;Samper-Villarreal et al, 2016;Belshe et al, 2017a,b;Dahl, 2017;Oreska et al, 2017a;Mazarrasa et al, 2018;Röhr et al, 2018). Sediment properties such as grain size, porosity, degree of sorting, and density are largely controlled by the hydrodynamic regime where, for instance, grain size typically increases with increasing wave-and current exposure, as the higher hydrodynamic energy and short residence times do not allow finer grains to settle (Folk and Ward, 1957;Fonseca and Bell, 1998;van Keulen and Borowitzka, 2003;Mazarrasa et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, sediment grain size is a strong predictor of sediment OM pools and seagrass sediments exhibit increases in both the amount of carbon stored Röhr et al, 2016;Samper−Villarreal et al, 2016;Miyajima et al, 2017) and carbon burial rates (Mazarrasa et al, 2017) with increasing silt-clay content. This correlation may be due to the larger surface area for adsorbing organic molecules at high silt-clay content (Keil et al, 1994;Bergamaschi et al, 1997), and low oxygen availability reducing the remineralization of OM (Dauwe et al, 2001;Serrano et al, 2016), as well as the relatively higher sedimentation of sestonic particles in these low-energy environments (Mazarrasa et al, 2017(Mazarrasa et al, , 2018. However, plant traits such as shoot density, above-and belowground biomass, and net primary productivity also explain a large part of the variability in carbon stock and sink capacity in local areas Gillis et al, 2017;Oreska et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%